2015
DOI: 10.1038/eye.2015.73
|View full text |Cite
|
Sign up to set email alerts
|

Long-term evaluation of dexamethasone intravitreal implant in vitrectomized and non-vitrectomized eyes with macular edema secondary to non-infectious uveitis

Abstract: Purpose To compare dexamethasone (DEX) intravitreal implant effect in nonvitrectomized (non-PPV) vs vitrectomized (PPV) eyes with macular edema (ME) secondary to non-infectious uveitis. Methods Medical records of patients with uveitic ME treated with DEX-intravitreal implant were reviewed. Main outcome measures were changes in central retinal thickness (CRT), best corrected visual acuity (BCVA), intraocular pressure (IOP), vitreous haze and adverse events. Statistical analysis was performed by Longitudinal Lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 19 publications
1
29
0
5
Order By: Relevance
“…However, there are several non-randomised trials, with 12-24 months of follow-up, that allow the use of repeat implants. 18,50,51 These studies consistently report that, after around 6 months, patients' outcomes return to those at baseline and that up to three repeat implants are each likely to have a similar treatment effect. Given the limited evidence around repeat implants, this was explored within sensitivity analysis.…”
Section: Interventionsmentioning
confidence: 71%
See 4 more Smart Citations
“…However, there are several non-randomised trials, with 12-24 months of follow-up, that allow the use of repeat implants. 18,50,51 These studies consistently report that, after around 6 months, patients' outcomes return to those at baseline and that up to three repeat implants are each likely to have a similar treatment effect. Given the limited evidence around repeat implants, this was explored within sensitivity analysis.…”
Section: Interventionsmentioning
confidence: 71%
“…18 Another study reported that the improvements in BCVA and central retinal thickness at 1 month were similar (not significantly different) following the first and second implants. 84 In a study of uveitis patients the median time from first to second implant was 10 months 50 whereas in four studies of uveitic macular oedema the mean/median time from first to second implant was 4.7, 81 5.0, 51 7.1 83 and 10 86 months. The mean time from second to third implant was 3.4 months in one study of uveitic macular oedema.…”
Section: Dexamethasone Studiesmentioning
confidence: 99%
See 3 more Smart Citations